Redescription of the adult male and description of second-instar male, prepupa and pupa of Ceroplastes japonicus Green (Hemiptera: Coccoidea: Coccidae) - Rainato, Alessio; Pellizzari, Giuseppina (Zootaxa, 2008)
The adult male of Ceroplastes japonicus Green is redescribed and illustrated and compared with other known males of Ceroplastes. In addition, the 2nd-instar male, male test, prepupa and pupa of C. japonicus are also described and illustrated for the first time.